THE CULTURE OF SPEECH AMONG TEACHERS AND LEADERS: ISSUES AND SOLUTIONS - Ubaydullayeva Bakhtigul; Abdumutalibova Kibriyo (TADQIQOTLAR, 2025)
Abstract: This article examines the significance of speech culture in the professional activities of teachers and leaders. Effective oral communication plays a crucial role in education and management, serving not only as a means of conveying information but also as a tool for influence, motivation, and leadership. The paper explores key aspects of speech etiquette, linguistic clarity, intonation, and the use of paralinguistic elements. Furthermore, the study highlights the importance of developing communicative competence in order to ensure successful interaction and enhance public speaking skills among professionals in teaching and leadership positions.